Social Support as a Predictor of Happiness in Undergraduate Students Working on Their Thesis - Michellyn Deviana Tan; Agnes Maria Sumargi (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2025)
Students who are working on a thesis generally experience anxiety not only related to their thesis research but also feel uncertainty about their future after graduating as a student. This has the potential to lower his level of happiness. Social support from family, friends, and close people can help students overcome anxiety, which can affect their happiness levels. This study aims to examine the influence of these social supports on the happiness of students who are working on their thesis. Given the possibility of differences in happiness based on gender, gender is considered in the analysis. The research participants were 205 students who were working on their thesis in Surabaya. Students participate by filling out online surveys using the Multidimensional Scale of Perceived Social Support and the Oxford Happiness Questionnaire which has been translated into Indonesian. The results of the regression analysis showed that only family support significantly affected the happiness of students and female students. Family support makes students view themselves positively and experience positive feelings that cause happiness so that they can face challenges in working on their thesis. Mahasiswa yang sedang mengerjakan skripsi umumnya mengalami kecemasan tidak hanya terkait dengan penelitian skripsinya tetapi juga merasakan ketidakpastian akan masa depannya setelah lulus sebagai mahasiswa. Hal ini berpotensi menurunkan tingkat kebahagiaannya. Dukungan sosial yang berasal dari keluarga, teman, dan orang terdekat dapat membantu mahasiswa mengatasi kecemasan, sehingga dapat mempengaruhi tingkat kebahagiaannya. Penelitian ini bertujuan untuk menguji pengaruh dukungan-dukungan sosial tersebut terhadap kebahagiaan mahasiswa yang sedang mengerjakan skripsi. Mengingat adanya kemungkinan adanya perbedaan kebahagiaan berdasarkan gender, maka gender diperhitungkan dalam analisis. Partisipan penelitian adalah 205 orang mahasiswa yang sedang mengerjakan skripsi di Surabaya. Mahasiswa berpartisipasi dengan mengisi survei secara daring menggunakan Multidimensional Scale of Perceived Social Support dan Oxford Happiness Questionnaire yang telah diterjemahkan ke dalam bahasa Indonesia. Hasil analisis regresi menunjukkan bahwa hanya dukungan keluarga yang mempengaruhi kebahagiaan mahasiswa maupun mahasiswi secara signifikan. Dukungan keluarga membuat mahasiswa memandang dirinya secara positif dan mengalami perasaan-perasaan yang positif yang menimbulkan kebahagiaan sehingga dapat menghadapi tantangan dalam mengerjakan skripsi.